Pengaruh Campuran Limbah Tongkol Jagung, Batang Singkong dan Batu Bara dengan Perekat Tapioka terhadap Kualitas Briket Biocoal - Aditia Haidar; Tamrin Tamrin; Sandi Asmara; R. A. Bustomi Rosadi (abe.fp.unila.ac.id, 2022)
Coal briquette is an alternative fuel or as a substitute for other fuels. Biocoal briquettes, the composition not only consists of calcium and adhesive but also added a mixture of biomass in it as a substance to reduce emissions and accelerate combustion. In making briquettes, it require adhesives to bind biomass and coal particles. The biomass use casson stone and corncob. This research purpose to determine the composition the waste mixed of corncob, cassion stone and coal with tapioca glues to be quality of biocoal briquettes. The method of this research is Completely Randomized Design Factorial. This research had two factors, the first factor (P) is comparison of composition material. The second factor (K) is composition of adhesive had three levels composition. Several experiment had repetition (U) by 3 times, with the result get 36 exprimental units. Result of research show the treatment of comparison of compostion material and adhesive is significant of density and shatter resistance value (p > 0,05). From result, treatment of P1K1 produced high density by 0,423 g/cm3. 13,89% from all of experimental units with bigger moisture content than 8% and 86,11% with under moisture content 8%. Optimal heating value produced of P4 by 5150,4 kal/g. The best of combustion rate produced of P2K1 and P4K1 by 0,43 g/minute. The base temperature of the pan base is 6 minutes start duration. Maximum temperature reach of every treatment P about 295-299 oC and minimum temperature is 256 oC and brickets of produce can keep with temperature on 180oC during 14 – 34 minutes. The treatment of P1K1 produce high shatter resistance index value by 99,75%.